PENGARUH BOARD CHARACTERISTICS TERHADAP ESG PERFORMANCE DENGAN FAMILY OWNERSHIP SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan yang terdaftar di Bursa Efek Indonesia Periode Tahun 2021-2023) - Dimas Farizki; Puji Harto (Diponegoro Journal of Accounting, 2025)
This study aims to examine and analyze the effect of Managerial Ability, CEO Tenure, and Board Diversity on ESG (Environmental, Social, and Governance) performance, with Family Ownership as a moderating variable. As control variables, this study also considers firm size, ROA (Return on Assets), and leverage.The study uses a moderated regression analysis approach to examine the relationships between these variables. Data were collected using a purposive sampling technique, with a sample of 58 companies listed on the Indonesia Stock Exchange during the period of 2021-2023.The results show that Managerial Ability, CEO Tenure, and Board Diversity do not have a significant effect on ESG performance. Furthermore, Family Ownership was found to moderate the relationship between board characteristicss and ESG performance. These findings contribute to the understanding of the factors influencing ESG performance in Indonesian companies and have implications for board governance policies and corporate sustainability strategies.